Dengue virus and the 2024 Paris Olympics - Zandi, Milad; Alizadeh, Ismaeil; Mousavi, Fatemeh Sadat; Faraji, Maryam (Frontiers in Public Health, 2024)
The 2024 Paris Olympics and Paralympics face concerns over dengue virus transmission, despite Paris’s lower mosquito activity. Preventive measures include eliminating breeding sites, insecticide spraying, and public awareness. Health systems will monitor and respond to cases. Large gatherings like the Olympics can amplify disease spread, as seen with Zika in Rio 2016. Recent reports confirm dengue presence in Europe, highlighting global risks. While Paris’s overall dengue risk is low, even a few cases could impact global health. Collaboration among health authorities, researchers, and event organizers is crucial to ensure participant and public safety during the games.